Benteng Amsterdam di Pesisir Utara Pulau Ambon: Tinjauan atas Aspek Kronologi dan Fungsi - Syahruddin Mansyur (Balai Arkeologi Maluku, 2015)
Fort Amsterdam is one of the fort in the fortifications system that was built by the VOC since the 17th century in the Maluku Islands. This research examines the micro aspects in the fortification system by focusing on the aspects of the chronology as well as the functions and roles of Fort Amsterdam. The bibliographical studies and the use of historical records also adopted in this study. The reslut of this research shows the chronology of the first fort built in 1629 as a trading post by VOC in the North Coast region of the island of Ambon. This fort then undergoes renovations both aimed to strengthen the defense function as well as trade and government functions in this fort. Amsterdam role both during and future VOC Dutch East Indies governement policies related to the clove monopoly on the Colonial period. Period of receding role of the fort was then happended along with the moment of the abolition of the clove monopoly by the Dutch in 1865.Benteng Amsterdam adalah salah satu benteng dalam sistem perbentengan yang dibangun oleh VOC sejak abad ke-17 di wilayah Kepulauan Maluku. Penelitian ini mengkaji aspek mikro dalam sistem perbentengan tersebut yaitu aspek kronologi serta aspek fungsi dan peran Benteng Amsterdam. Melalui kajian kepustakaan yang bersumber dari catatan-catatan historis, serta hasil penelitian terdahulu. Penelitian ini berhasil mengungkap kronologi benteng yang pertamakali dibangun pada tahun 1629 sebagai pos perdagangan VOC di wilayah Pesisir Utara Pulau Ambon. Benteng ini kemudian mengalami beberapakali renovasi yang bertujuan untuk memperkuat fungsi pertahanan serta fungsi perdagangan dan pemerintahan pada benteng ini. Peran Benteng Amsterdam pada masa VOC dan masa Pemerintah Hindia Belanda berhubungan dengan kebijakan monopoli cengkih pada masa Kolonial. Periode surut peran benteng ini kemudian mulai terjadi pada periode penghapusan monopoli cengkih oleh Belanda pada tahun 1865.